Exploiting Lithium‐Depleted Cathode Materials for Solid‐State Li Metal Batteries. Issue 28 (24th June 2019) - Wang, Li‐Ping; Wang, Tai‐Shan; Yin, Ya‐Xia; Shi, Ji‐Lei; Wang, Chun‐Ru; Guo, Yu‐Guo
Abstract: Solid‐state lithium metal batteries (SSLMBs) may become one of the high‐energy density storage devices for the next generation of electric vehicles. High safety and energy density can be achieved by utilizing solid electrolytes and Li metal anodes. Therefore, developing cathode materials which can match with Li metal anode efficiently is indispensable. In SSLMBs, Li metal anodes can afford the majority of active lithium ions, then lithium‐depleted cathode materials can be a competitive candidate to achieve high gravimetric energy density as well as save lithium resources. Li0.33 MnO2 lithium‐depleted material is chosen, which also has the advantages of low synthesis temperature and low cost (cobalt‐free). Notably, solid‐state electrolyte can greatly alleviate the problem of manganese dissolution in the electrolyte, which is beneficial to improve the cycling stability of the battery. Thus, SSLMBs enable practical applications of lithium‐depleted cathode materials. Abstract : A Li0.33 MnO2 lithium‐depleted cathode is combined with a lithium metal anode and a solid electrolyte as a solid‐state lithium metal battery (SSLMBs). In SSLMBs, the Li metal anode can afford active lithium ions, thus lithium‐depleted material can be a competitive candidate as the cathode. This work demonstrates the possibility of using lithium‐depleted materials and broadens the choice of cathode materials for SSLMBs.